Bjarmaland - Koskela Vasaru, Mervi (Oulu : University of Oulu, 2016)
Bjarmaland (also Biarmaland, Biarmia, Byarmia, Bjarmia) and its inhabitants (Bjarmar, Beormas, Biarmar) are known to us through c. 30 medieval written sources, most of them written in Norse, a few in Latin and one in Anglo-Saxon. Majority of the texts were written during the 13th century, but the stories they relate may nevertheless be of earlier date. The Kings' Sagas in particular often refer to 10th century events. Oldest of the sources is the so-called Ohthere's account, a 9th century Anglo-Saxon text added to the OE Orosius translation. The rest of the sources are of Norse-Icelandic origin including a number of konungasögur, a few chronicles and íslendingasögur, some texts of geographical nature, a couple of þáttr, and a number of fornaldarsögur as well as six annals. Additionally Haralds saga gráfeldar contains a few skaldic verses.Written sources locate Bjarmaland to the White Sea. The words Terfinna land connect the location with the Kola Peninsula and the environs of the Varzuga River whereas the name Gandvík guides our interest towards the Kantalahti Bay of the White Sea. The name 'Vína' can be connected with either the Northern Dvina River or Viena Karelia. Written sources portray the Bjarmians as permanently settled group of Baltic Fennic speaking people that lived in the north of Europe since the Viking Age (first mentioned in writing in the 9th century) until the early Middle Ages (mid-13th century). Involvement in the international fur trade is implied and continuous contacts with Norwegians with both looting and trade as integral part of interaction are present in the descriptions. The Bjarmians cannot be connected ethnically with any existing group of people but must be considered as a group of their own. The origin of the specific ethnical identity most likely lies in economical interaction (trade with furs and possibly other items) with neighbouring areas. Since 12th-13th centuries new settlers moved to the northern areas and many political and economical changes occurred in Northern Fennoscandia and Russia, all of which would have contributed to a change that left the Bjarmians out of written sources.
Bjarmaland (myös Biarmaland, Biarmia, Byarmia, Bjarmia) ja sen asukkaat (Bjarmar, Beormas, Biarmar) tunnetaan noin kolmestakymmenestä keskiaikaisesta kirjallisesta lähteestä, joista useimmat on kirjoitettu islanniksi, muutamat latinaksi ja yksi anglosaksiksi. Suurin osa teksteistä kirjoitettiin 1200-luvulla, mutta niiden sisältö voi koskea aiempia tapahtumia. Erityisesti kuningassaagat viittaavat usein 900-luvun tapahtumiin. Vanhin lähteistä on niin sanottu Ohtheren kertomus, joka on 800-luvulla kirjoitettu lisäys Orosiuksen maailmanhistorian anglosaksiseen käännökseen. Muut lähteet ovat islantilais-norjalaista alkuperää ja koostuvat useista kuningassaagoista sekä muutamasta islantilaissaagasta, maantieteellisistä teksteistä, parista þáttrista että joukosta muinaissaagoja ja annaaleja. Lisäksi Haralds saga gráfeldarissa on mukana skaldirunouden säkeitä. Kirjalliset lähteet sijoittavat Bjarmalandin Vienanmerelle. Sanat Terfinna land liittävät sijainnin Kuolan niemimaahan ja Varzugajoen ympäristöön kun taas nimi Gandvík ohjaa mielenkiinnon kohti Kantalahtea. Nimi 'Vína' voidaan yhdistää joko Vienajokeen tai Vienan Karjalaan. Kirjalliset lähteet kuvaavat bjarmeja pysyvästi asuvina itämerensuomalaista kieltä puhuvina ihmisinä, jotka asuivat Pohjois-Euroopassa viikinkiajalta (ensimmäinen kirjallinen maininta on peräisin 800-luvulta) keskiajalle (1200-luvun puoliväliin). Lähteet vihjaavat bjarmien olleen mukana kansainvälisessä turkiskaupassa ja jatkuvat kontaktit norjalaisiin joko kaupankäynnin tai ryöstelyn merkeissä ovat tärkeässä osassa lähteiden kertomuksissa. Bjarmeja ei voi etnisesti liittää mihinkään nykyiseen ihmisryhmään vaan heitä täytyy pitää omana erillisenä ryhmänään. Etnisen identiteetin synty liittyy todennäköisimmin kaupankäyntiin (turkikset ja mahdolliset muut kauppatavarat) naapureiden kanssa. Alkaen 1100- ja 1200-luvuilta pohjoiselle alueelle muutti uutta väestöä ja samaan aikaa pohjoisessa Fennoskandiassa ja Venäjällä tapahtui monia poliittisia ja taloudellisia muutoksia ja näiden yhteisvaikutus todennäköisesti johti osaltaan siihen, että bjarmit jäivät pois kirjallisista lähteistä.
Bjarmaland.
Tiivistelmä.
Aims, methods and sources -- Bjarmaland in historiography -- Early contacts -- Battles, trade and geography -- Tradition and fantasy -- Bjarmaland in early medieval landscape.
Perustuu osin tekijän väitöskirjaan.
Väitöskirja
Julkaistu myös verkkoaineistona.
Keywords: etninen identiteetti; historia; historiankirjoitus; itämerensuomalaiset kansat; kauppa; kirjalliset lähteet; muinaiskansat; saagat; suomalais-ugrilaiset kansat; viikinkiretket; etnisk identitet; historia; historieskrivning; östersjöfinska folk; handel; skriftliga källor; forntidsfolk; fornnordiska sagor; finsk-ugriska folk; vikingafärder; Bjarmalanti; Kantalahti; Kuolan niemimaa; Vienanmeri; Bjarmaland; Kandalaksja; Kolahalvön; Vita havet